2009
DOI: 10.1007/s00024-008-0428-3
|View full text |Cite
|
Sign up to set email alerts
|

Field Survey and Geological Effects of the 15 November 2006 Kuril Tsunami in the Middle Kuril Islands

Abstract: Abstract-The near-field expression of the tsunami produced by the 15 November 2006 Kuril earthquake (M w 8.1-8.4) in the middle Kuril Islands, Russia, including runup of up to 20 m, remained unknown until we conducted a post-tsunami survey in the summer of 2007. Because the earthquake occurred between summer field expeditions in 2006 and 2007, we have observations, topographic profiles, and photographs from three months before and nine months after the tsunami. We thoroughly surveyed portions of the islands of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The transportation of beach gravels towards backshore and inland areas often occurs during modern tsunamis, and has been documented from the 1993 Hokkaido Nansei‐oki tsunami (Sato et al, ), the 2001 Perú tsunami (Jaffe, Rubin, & Peters, ), the 2006 Kuril Tsunami (MacInnes et al, ), and the 2011 Tohoku tsunami (Nishina, Kawakami, & Tajika, ). Hirakawa et al () revealed the ages of prehistoric tsunamis and their recurrence intervals along the Pacific coast of eastern Hokkaido from the stratigraphy of cobbly deposits in the surficial soils of marine terraces.…”
Section: Discussionmentioning
confidence: 99%
“…The transportation of beach gravels towards backshore and inland areas often occurs during modern tsunamis, and has been documented from the 1993 Hokkaido Nansei‐oki tsunami (Sato et al, ), the 2001 Perú tsunami (Jaffe, Rubin, & Peters, ), the 2006 Kuril Tsunami (MacInnes et al, ), and the 2011 Tohoku tsunami (Nishina, Kawakami, & Tajika, ). Hirakawa et al () revealed the ages of prehistoric tsunamis and their recurrence intervals along the Pacific coast of eastern Hokkaido from the stratigraphy of cobbly deposits in the surficial soils of marine terraces.…”
Section: Discussionmentioning
confidence: 99%
“…Numerical tsunami models are frequently validated using only wave height and inundation data, which is now plentiful from recent events (e.g., Liu et al (2005); Synolakis and Okal (2005); Satake et al (2006); MacInnes et al (2009MacInnes et al ( , 2013; Okal et al (2010); Fritz et al (2011)), Surface elevation from Deep-Ocean Assessment and Reporting of Tsunamis (DART) buoys or other deep-ocean monitors as well as from coastal and harbor tide gauges are used, along with inundation and runup data collected by tsunami survey teams following every major event (e.g., Synolakis et al (2007); Apotsos et al (2011)). See in particular the work of Tang et al (2009), which concerns validation of the MOST tsunami model using data around Hawaii from several past tsunamis.…”
Section: Introductionmentioning
confidence: 99%
“…-We assign a yellow (average) index to the 2006 Kuril Islands earthquake. Even though no casualties were suffered from either the seismic event or the tsunami, this was due to the extreme remoteness of its unpopulated epicentral area, where the 21 m run-up was surveyed only nine months after the event [90]. In the far field, the handling of the warning was nothing short of a failure, with both PTWC and WCATWC repeatedly issuing statements of 'no warning' or even 'no watch', despite the significant moment of the earthquake (M 0 = 3.5 × 10 28 dyn cm).…”
Section: (A) Events From 2004 To 2010mentioning
confidence: 99%